Technology Integration and Community Empowerment in Smart Villages: Bibliometric Analysis - Darlis, Muh Akbar Ali; Ikbal, Muhammad; Lubis, Sandi; Ali, Akhwan (Department of Government Studies, Universitas Muhammadiyah Buton., 2025)
This research explores the concept of Smart Villages, focusing on the challenges and opportunities in their implementation in rural areas. The study emphasizes social sustainability, community empowerment, and the role of technology in improving quality of life. The objectives are twofold: to understand the role of international collaboration in accelerating smart village development and to explore the implications of these findings for future development. Bibliometric analysis is used to map research progress and identify strategies for integrating technology into smart village management. The findings offer practical implications for public policy design, showing the potential for creating more inclusive and sustainable strategies for smart village implementation. The study highlights the importance of cross-sector collaboration and empowering village communities in policy planning and execution. It also provides insights into addressing challenges related to technology application in rural areas, as well as improving social and environmental sustainability through technology-driven solutions. This research contributes by combining technical, social, and cultural analysis in the development of smart villages. Its value lies in a holistic approach, considering social, cultural, and economic diversity when designing solutions. Additionally, it fills gaps in existing literature by incorporating international perspectives, with a special focus on developing countries.